Association between apolipoprotein E e4 allele and arteriosclerosis, cerebral amyloid angiopathy, and cerebral white matter damage in Alzheimer's disease. Issue 5 (16th April 2004) - Tian, J; Shi, J; Bailey, K; Lendon, C L; Pickering-Brown, S M; Mann, D M A
Abstract : Objective: To investigate the association between white matter damage, as evidenced by myelin loss (ML), the extent of cerebral amyloid angiopathy (CAA), or arteriosclerosis (Art), and apolipoprotein E (ApoE) e4 allele in Alzheimer's disease (AD), in order to understand the causes of damage to white matter in AD and its contribution to the pathogenesis of the disorder. Materials and methods: Brain tissues were obtained from 94 patients with AD confirmed by autopsy. ApoE genotyping was performed by PCR on DNA extracted from frontal cortex or cerebellum. CAA and Art were assessed on Weigert's haematoxylin and eosin stained sections in frontal, temporal, parietal, and occipital cortices; the extent of ML was scored on Luxol fast blue stained sections of these regions. Results: The ApoE e4 allele frequency in the 61 patients with ML was not significantly different from that in the 33 patients without ML, nor did this differ in the 84 patients with Art from that in the 10 patients without Art. There were no significant differences in the proportions of patients with genotypes containing 0, 1, or 2 ApoE e4 alleles in the presence or absence of ML or Art. The mean ML, Art, or CAA scores within each region, and the total scores summed across all four brain regions, did not differ between patients with 0, 1, or 2 ApoE e4 alleles. However, the mean ML severity score in the occipital cortex was significantly greater than that in the frontal or temporal cortices in patients with 1 or 2 ApoE e4 alleles. The severity of CAA in the occipital cortex was significantly higher than that in other areas of cortex in patients with 0 or 2 ApoE e4 alleles. The mean Art score in the occipital cortex was greater than that in the temporal cortex in patients with two ApoE e4 alleles and was higher than that in the frontal cortex in patients with one ApoE e4 allele. Conclusions: The likelihood of patients with AD suffering from CAA, Art, or ML is not influenced by ApoE e4 allele, nor is the overall burden of these pathological changes in the brain. However, the distribution of ML, CAA, and Art within the brain is at least partly influenced by genotype and dosage of ApoE e4 allele, with the occipital cortex being more severely affected by all of these pathological changes in e4 allele bearers, particularly when two ApoE e4 alleles are present.